ANALISIS FAKTOR PELANGGARAN PENGENDARA RODA DUA PADA LALU LINTAS SIMPANG BERSINYAL JALAN POROS PINRANG POLMAN - Amir, Nasruddin; Rahmawati, Rahmawati; Fadly, Imam (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2024)
Traffic violations are one of the problems that trigger that can disturb road users, especially at signalized intersections on the Pinrang Polman axis, Bungi Village, Duampanua District, Pinrang Regency. This research aims to determine the factors that cause violations by two-wheeled drivers and provide alternative solutions to the problem of violations by two-wheeled drivers at signalized traffic intersections using questionnaire survey method. The results of the analysis using SPSS from the 100 sample questionnaires distributed showed that the human factor (X1) with coefficient value of 0.010 has a very low influence on the variable that causes violations (Y), the vehicle factor (X2) with coefficient value of 0.080 has a very low influence on the variable causing the violation (Y) and the signalized intersection factor (X3) with coefficient value of 0.937 has a very strong influence on the variable that causes violations (Y). An alternative for handling violations by two-wheeled drivers is to provide education regarding traffic rules, the application of technology and traffic monitoring systems.